A wireless monitoring system for measuring flexible tank strain using fabric-based stretchable conductive sensor - Muhammad Razif, Muhammad Rusydi; Jaafar, Nur Jannah; Mohd Mustapha, Nurul Hasyimah; Yong Tze Mi, Yong Tze Mi; Mohd Shah, Nor Shahida; Hashim, Muhamad Mohshein; Mustaffa, Khairul Nizam (2024)
The logistics shipping industry using flexible tanks is one of the shipping industries that has grown globally. Flexible tanks are flexible containers that are usually made of polymers that can be used to transport liquids such as oil and chemicals and are usually loaded in cargo. During shipping, liquids with a large free surface area will experience sloshing due to external induced forces whether transported by land or sea. Uncontrolled sloshing is known to damage flexible tanks and cause leaks where cargo is not only wasted but can damage shipping containers, spill over other shipping containers and cause unwanted environmental pollution. This project aims to investigate the part of the tank that will provide high pressure by using a stretchable strain sensor. The project will also develop a wireless flexible tank monitoring system to continuously monitor the condition of the tank in real time. The resulting tension on the tank due to movement during shipping will be analyzed using a conductive stretchable sensor through the resistance and force data. This project will be implemented using a conductive stretchable sensor, an ESP32 microcontroller, an ESP32 camera, and a Blynk server. The sensor will be installed on a certain part of the flexible tank which is expected to produce a high strain force and then give a reading of the resulting force on that part. Based on the results, this project shows that the developed monitoring system can efficiently analyze the resistance and forces occurring in the flexible tank in real time.